1990
DOI: 10.1104/pp.93.4.1466
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Factors in Photosynthesis

Abstract: Earlier work (SE Taylor, N Terry [1984] 86) has shown that the rate of photosynthesis may be colimited by photosynthetic electron transport capacity, even at low intercellular CO2 concentrations. Here we monitored leaf metabolites diumally and the activities of key Calvin cycle enzymes in the leaves of three treatment groups of sugar beet (Beta vulgaris L.) plants representing three different in vivo photochemical capacities, i.e. Fe-sufficient (control) plants, moderately Fe-deficient, and severely Fe-defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 36 publications
(41 reference statements)
2
13
0
1
Order By: Relevance
“…Cleared lysates corresponding to 8 mg of fresh weight were subjected to SDS/PAGE and blotted onto nylon membranes for immunodetection of Fd, Fld, light-harvesting chlorophyllbinding protein (LHCP), and Rubisco large (LSU) and small (SSU) subunits. agreement with previous observations (10)(11)(12)(13). The presence of Fld in chloroplasts, but not in the cytosol, almost entirely prevented this decline (Fig.…”
Section: Fld Accumulation Prevents the Decline Of Photosynthetic Compsupporting
confidence: 82%
See 3 more Smart Citations
“…Cleared lysates corresponding to 8 mg of fresh weight were subjected to SDS/PAGE and blotted onto nylon membranes for immunodetection of Fd, Fld, light-harvesting chlorophyllbinding protein (LHCP), and Rubisco large (LSU) and small (SSU) subunits. agreement with previous observations (10)(11)(12)(13). The presence of Fld in chloroplasts, but not in the cytosol, almost entirely prevented this decline (Fig.…”
Section: Fld Accumulation Prevents the Decline Of Photosynthetic Compsupporting
confidence: 82%
“…Total RNA was extracted from 1 g of plant material with the TRIzol reagent (Invitrogen, Paisley, U.K.). Synthesis of cDNA was carried out on 1 g of RNA by using the SuperScript III RT kit and oligo(dT) [12][13][14][15][16][17][18] primers of Invitrogen, as indicated in the instruction manual. Semiquantitative RT-PCR analysis was performed as described (18), with the optimal number of cycles determined for each gene to analyze expression in the exponential phase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result differs from that reported by Thoiron and Briat (1999), who showed that leaf sucrose content remained unchanged under Fe deficiency. However, other authors (Arulanantham et al 1990) recorded a decrease in sucrose accumulation in leaves of sugar beet plants under moderate or severe Fe deficiency.…”
Section: Discussionmentioning
confidence: 90%